IMPLEMENTING THE PROBLEM BASED LEARNING MODEL BASED ON THE LOCAL WISDOM OF HOMBO BATU TO ENHANCE STUDENTS’ PHYSICS PROBLEM-SOLVING SKILLS AT SMA NEGERI 1 FANAYAMA - Darmawan Harefa (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2026)
This study aims to examine the effectiveness of the implementation of the Problem Based Learning (PBL) model based on the local wisdom of Hombo Batu in improving students’ physics problem-solving abilities at SMA Negeri 1 Fanayama. The research employed a quasi-experimental method with a pretest–posttest control group design. The participants consisted of tenth-grade students who were divided into an experimental class and a control class. The experimental class received instruction using the Problem Based Learning model integrated with the cultural context of Hombo Batu, while the control class was taught using conventional learning methods. Data were collected through a physics problem-solving test administered before and after the learning process. The results showed that students in the experimental class experienced a significant improvement in their problem-solving abilities compared to those in the control class. The normalized gain score of the experimental group was higher than that of the control group, indicating that the implementation of the PBL model provided a more effective learning experience. In addition, integrating the Hombo Batu cultural context helped students understand physics concepts more meaningfully because the learning materials were related to real-life cultural practices familiar to the students. Therefore, the integration of Problem Based Learning with local wisdom can create contextual and meaningful physics learning while also fostering students’ appreciation of local cultural heritage.